Clinimetric methods for evaluating patients with Parkinson's disease in the context of the latest treatment strategies - Pawłowski, Piotr; Ziętara, Karolina; Orzechowska, Aleksandra; Pawlina, Mateusz; Pawełczak, Natalia; Oskroba, Aleksander; Stawikowski, Cezary; Raksa, Karolina; Kowalczyk, Ilona; Zielonka, Bartłomiej (Journal of Education, Health and Sport, 2023)
Background: Parkinson's disease is a neurodegenerative disease involving the deposition of alpha-synuclein deposits in dopaminergic neurons of the black matter, resulting in a decrease in dopamine levels in the central nervous system and the development of motor and non-motor symptoms. Aim of the study: This study aims to identify clinimetric methods for evaluating patients with Parkinson's disease in the context of contemporary therapies. Material and methods: English-language scientific literature from 2012 - 2022 from databases such as PubMed, SCOPUS, Web of Science, Google Scholar was reviewed. Searches were conducted according to keywords: Parkinson's disease, clinical evaluation, and treatment methods. 69 items of literature were qualified for analysis. Results and conclusions: The diagnosis of Parkinson's disease is a diagnosis by exclusion, there are no available and inexpensive methods to diagnose the disease with certainty. The clinimetric assessment of the patient is therefore the basis not only for diagnosis but also for effective, tailored treatment. There are many assessment tools dedicated to patients with this disease entity, and these are the ones recommended for this process. Contemporary treatment methods, especially for those in whom the effectiveness of pharmacological treatment is unsatisfactory, include deep brain stimulation, enteral infusion of DuoDopa®, and subcutaneous infusion/injections of apomorphine. The inclusion of the techniques depends mainly on the assessed condition of the patient.